Unfettered Discretion: Criminal Orders of Protection and their Impact on Parent Defendants - Jaros, David Michael (2010)
The last two decades have witnessed an astonishing increase in the use of the criminal justice system to police neglectful parents. Recasting traditional allegations of neglect as criminal charges of endangering the welfare of a child, prosecutors and the police have involved criminal courts in the regulation of aspects of the parent-child relationship that were once the sole province of family courts. This Article explores the legal implications of vesting judges in these cases with the unfettered discretion to issue protective orders that criminalize contact between a parent and her child.I argue that procedures for issuing protective orders that were once justified by the challenges of fighting domestic violence cannot constitutionally be applied to parents charged with criminal neglect. Instead, criminal courts and legislatures should look to family court, the forum traditionally empowered to police neglectful parents, for guidance on how to properly intervene on behalf of neglected children